Traversing moral shifts in adolescent education: insights from some rural south african secondary schools - Oratilwe Penwell Mokoena; Solly Matshonisa Seeletse (Indonesian Counselor Association (IKI), 2023)
The continuously evolving moral standards ‘new morality’ have emerged, particularly among the young people due to past prejudices. The paper investigates the teaching challenges experienced by educators who encounter adolescent learners influenced by ‘new morality’. The study focused on adolescents in rural secondary schools in three provinces, where 137 teachers from several different schools were surveyed. The findings suggest that new morality is often viewed more as a modern form of morality embraced by young people, rather than simply as misbehavior. As a result, teachers may mistakenly interpret the behaviors associated with new morality as defiance, when in fact the students are not necessarily acting out. Most teachers reported that the behaviors of these new morality-influenced adolescents made teaching quite difficult, and they called for policy changes to give them more control over the classroom. However, the teachers also recognized that for new morality not to disrupt the school system, new rules would need to be developed. The paper highlights the tensions and challenges that educators face in navigating the evolving moral landscape of their adolescent students.